An empirical evidence of audit firm merger and audit pricing in Malaysia - Hariri, Hilwani; Abdul Rahman, Norshimah; Che Ahmad, Ayoib (MCB UP Ltd, 2007)
The merger of PriceWaterhouse and Coopers & Lybrand marked another historical event in the accounting and auditing industry. Both firms were optimistic that the merger would enhance the performance as well as the profession of the merged firms. This research studies the impact of the merger and the price of audit service charged to their clients. The findings showed that there is no significant impact of the merger on audit pricing. The results provide richer understanding of the relationship between organizational structure and pricing in a developing country.